Pengaruh Model Mengajar Menginduksi Perubahan Konsep Simson Tarigan dan Problem Based Learning dengan Media Ms Frontpage Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Kimia - Nesfi Vayuni; Simson Tarigan; Retno Dwi Suyatni (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. This study aims to know: (1) The effect of M3PK and PBL using MS Frontpagemedia to students’ critical thinking ability. (2) The effect of M3PK and PBL using MS Frontpagemedia to students’ learning outcomes. (3) Interaction between M3PK and PBL usingMS Frontpagemediawith critical thinking abilityon effect ofstudents’ learning outcomes.The population in this study is all students in siswa di SMA Negeri 1 Labuhanhaji Barat of the school year 2014/2015. Sampling techniquewas   purposive sampling. The sample in this study consisted of 2 class that are XI-IPA I and XI-IPA 2. XI-IPA I class as experiment class 1 taught with M3PK using Ms Frontpage media. XI-IPA 2 class as experiment class 2 taught with PBL using Ms Frontpage media. The study instrument in the form an objective test of learning outcome and observation sheet of students’ critical thinking ability. The data analysis performedbytheGeneralLinear Models(GLM)Univariate using SPSS 16.0 programe. Theresults showedthat: (1) There are significant effect of M3PK and PBL with usingMs Frontpagemedia on students’ critical thinking ability. (2) There are significant effect of M3PK and PBL with usingMs Frontpagemedia on students’learning outcomes. (3) There are no interaction between learning models with students’ critical thinking ability in affecting student learning outcomes. Keywords: model of teaching to induce the conceptual change, problem based learning, Ms.frontpage, learning outcome, critical thinking ability